Conservation of Djemevies within the Context of Faith-Space Relationship: Malatya Arapgir Onar Village’s Djemevies - Olğun, Tuba Nur; Akyildiz, Nihal Arda (Ankara Haci Bayram Veli University, 2021)
Faith has been one of the most basic needs/instincts of people in the progression from past to present. Throughout history, many societies have developed their belief dynamics; has built their sacred belief systems and rituals. In this context, the way of approaching God, which forms the basis of sacred belief systems, has led to the design of unique spaces needed to perform rituals in some religious systems. It is possible to find traces, structures and symbols of many religions and sects in Anatolia, which has hosted many civilizations with its ancient past. In this context, Alevi culture and belief, which stands out with its lively and active elements in Anatolian culture, and its unique sacred places have been the subject of many scientific studies in terms of historical, political and cultural aspects. In the Alevi tradition, djemevies, which host religious events (supplication, Public ring prayer, sacrifice, semah, etc.) as well as supporting the socio-cultural solidarity system, have an important place in Alevi belief and worship. From this point of view, the aim of the study is to consider the value of djemevi structures in Alevi culture in the context of sacred religious places and to draw attention to the necessity of conserving these structures. The study aims to present the original spatial value of two traditional structures, whose original function was a dervish lodge, but which were re-functionalized as a djemevi, in the rural settlement area of Onar, located in the Arapgir district of Malatya province, which was selected to examine the subject within the scope of the conservation of religious buildings, together with literature research and field studies. © 2021 Ankara Haci Bayram Veli University. All rights reserved.
İNANÇ-MEKÂN İLİŞKİSİ BAĞLAMINDA CEMEVLERİNİN KORUNMASI: MALATYA ARAPGİR ONAR KÖYÜ CEMEVLERİ
Keywords: Arapgir; Conservation; Djemevi; Malatya; Places of Belief; Religious Buildings